The implementation of binding blocks in the classroom. (29th June 2017) - Wright, A J; Willett, H V; Beanland, S R; Carson, M; Davies, R A; Duffett, G; Pastore, A
Abstract: We discuss a series of activities for A-level students which can be carried out using the binding blocks three dimensional chart of nuclides. The planned activities cover four main sections which can be linked to the A-level curriculum; nuclear decays (as seen through the different colours on the chart), medical physics (medical isotopes highlighted on the chart), fusion on Earth (binding energy demonstrated through tower heights) and stellar fusion (which has a limit at 56 Fe, illustrated by the decreasing tower heights).